2014
DOI: 10.4172/2157-7579.1000153
|View full text |Cite
|
Sign up to set email alerts
|

Body Surface Changes in Gastrointestinal Helminthes Following in vitro Treatment with Allium sativum Oil

Abstract: A scanning electron microscopic study was undertaken to assess, for the first time, whether Allium sativum oil (ASO) extract had any effect on helminthes' body surface following 24 h incubation in vitro. Two species of gastrointestinal helminthes, of most economic significance in sheep, Haemonchus contortus and Moniezia expansa were collected from naturally infected sheep slaughtered in Cairo abattoir, then exposed to 10, 50, 100 µg/ml ASO. The body surface of these helminthes was observed to be affected and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…The current observations appeared to be parallel with that demonstrated by previous histomorphological studies about the nematodes' cuticle where this was detected to be a main target organ for many synthetic and natural anthelmintics (Martin et al 1997;Kandil et al 2023). The cuticular distortion of the adult H. contortus induced by coriander essential oil had been reported for these nematodes by a number of anthelmintics (Shalaby et al 2014). Taken together, our data showed that coriander and geraniol had potential anthelmintic activity and could be used against gastrointestinal nematodes particularly H. contortus.…”
Section: Discussionsupporting
confidence: 88%
“…The current observations appeared to be parallel with that demonstrated by previous histomorphological studies about the nematodes' cuticle where this was detected to be a main target organ for many synthetic and natural anthelmintics (Martin et al 1997;Kandil et al 2023). The cuticular distortion of the adult H. contortus induced by coriander essential oil had been reported for these nematodes by a number of anthelmintics (Shalaby et al 2014). Taken together, our data showed that coriander and geraniol had potential anthelmintic activity and could be used against gastrointestinal nematodes particularly H. contortus.…”
Section: Discussionsupporting
confidence: 88%
“…Consequently, passive diffusion of anthelmintic drugs through the worm body wall might be the main reason for damaging alterations and disfiguration of the helminthes' body surface [20,21]. Parallel to the current observations, the helminthes' body surface was noticed to be a main objective organ for several synthetic and natural anthelmintics as evidenced by previous histomorphological studies [1,[22][23][24]. The swelling and distortion of the body surface of the examined helminthes induced by Balanites extract had been previously described for these helminthes by a number of anthelmintics [1,25].…”
Section: Discussionsupporting
confidence: 82%
“…Similar cuticular changes were observed in Chrysomyia albiceps larvae treated with spinosad; a metabolite of actinomycete Saccharopolyspora spinosa, ginger roots of Zingiber officinale and garlic fruits of Allium sativum (Shams El-Din 2010) as well as C. megacephlala treated with volatile oils of Eucalytal eucalyptal (Sukontason et al 2004) and neem extract (Siriwattanarungsee et al 2008). Comparable swelling, blebbing and distortion of the body cover in intestinal and liver parasites were observed following treatment with essential oils of myrrh (Massoud et al 2012), Nigella sativa Shalaby and El-Moghazy 2013) and Allium sativum (Shalaby and Farag 2014).…”
Section: Discussionmentioning
confidence: 98%